2021
DOI: 10.25259/ijasm_15_2021
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity through Night Vision Goggles (NVGs): A comparative assessment between Gen 2++ and Gen 3 NVGs under different illumination conditions

Abstract: Introduction: During night flying operations, Night Vision Goggles (NVGs) help the aircrew to visualize by intensifying lights reflected from an object. Night sky illumination and image intensification mechanism are the two important factors that affect visual acuity (VA) through NVG. Hence, assessment of visual acuity through Gen 2++ and Gen 3 NVG under different illumination conditions and comparative analysis between the two NVGs was the desired objective of the study. Material and Methods: In a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…VA has been commonly used to compare visual performance of NVG under different conditions of illumination and varying contrast. [3,6] In this study, VA performance for ANVIS Mk-III NVG showed decreasing trend with decreasing illumination [Table 2]. This is expected with any NVG and is due to increase in noise due to decreasing illumination.…”
Section: Visual Acuitymentioning
confidence: 54%
See 2 more Smart Citations
“…VA has been commonly used to compare visual performance of NVG under different conditions of illumination and varying contrast. [3,6] In this study, VA performance for ANVIS Mk-III NVG showed decreasing trend with decreasing illumination [Table 2]. This is expected with any NVG and is due to increase in noise due to decreasing illumination.…”
Section: Visual Acuitymentioning
confidence: 54%
“…This is expected with any NVG and is due to increase in noise due to decreasing illumination. [1,3] However, when compared to other NVGs [Figure 5], VA was found to be consistently better even in low light illumination like the QM and SL conditions. This is an interesting finding and is definitely advantageous in target resolution under varying illumination conditions.…”
Section: Visual Acuitymentioning
confidence: 83%
See 1 more Smart Citation